Information services at airports as an educational service: a servqual-based study at Adi Soemarmo Airport - Andi Batari Toja; Chesya Agnestya Koagouw; Pahotan F. Roy Nainggolan; Rifqi Raza Bunahri (Educenter : Jurnal Ilmiah Pendidikan, 2026)
This study was motivated by the growing need for responsive and informative airport information services, yet challenges persist regarding the clarity of signage, the effectiveness of information dissemination, and passenger understanding at Adi Soemarmo Airport. The objective of this study is to measure passenger satisfaction with information services using the Service Quality (Servqual) method. This study employs a descriptive quantitative approach with a population of 2,222 average monthly passengers in May 2025 and a sample of 100 respondents. Data were collected via a Google Forms questionnaire and analyzed using Microsoft Excel. The results indicate that four attributes are rated as “very good,” four as “good,” and three as “needing improvement.” The average gap value was 0.335 with a satisfaction rate of 82.05%, indicating that the majority of passengers were satisfied. However, improvements in physical and visual information media, such as signage and information displays, are still needed to strengthen the educational function and enhance passenger understanding more effectively.